Isolation of Arcanobacterium Haemolyticum in Semen of an Infertile Patient - Penna-Videau, Salvador; Cermeño, Julman; Padrón-Medina, Aracelis (Investigación Clínica, 2009)
This is the report of a genital tract infection caused by Arcanobacterium haemolyticum in an infertile man from Venezuela. This 29 year-old patient was evaluated for primary infertility, without symptoms of seminal infection. Laboratory analysis showed leukocytospermia, low sperm count, motility and vitality, without abnormalities in hormonal profile. Sperm culture was positive for A. haemolyticum. After erythromycin therapy an improvement in some sperm parameters was observed. A. haemolyticum could be considered as a cause for silent seminal infection